2021
DOI: 10.2169/internalmedicine.5677-20
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Keishibukuryogan in Subcutaneous Hematoma after Implantable Cardiac Device Surgery in Two Cases

Abstract: Keishibukuryogan is a Kampo medicine that induces vasodilation and improves the blood flow velocity in subcutaneous blood vessels. We herein report two cases in which keishibukuryogan completely diminished subcutaneous hematoma after cardiac resynchronization therapy pacemaker implantation and defibrillator battery replacement within a month. Keishibukuryogan can be a good option for treating or preventing subcutaneous hematoma after surgical procedures for devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They were attached to adipose (Ad) tissues on their outer, while their inner surfaces (adjacent to implant) were smooth, slippery, and lined with interstitial fluid [18, 42]. Localized blood patches (subcutaneous hematoma) were observed on inner sides in 3/5 (60%) and 1/2 (50%) of Fb-P (samples 1, 3, and 5) and Fb-PECM (1), likely due to the surgical procedure [43]. No signs of swelling were noticed.…”
Section: Resultsmentioning
confidence: 99%
“…They were attached to adipose (Ad) tissues on their outer, while their inner surfaces (adjacent to implant) were smooth, slippery, and lined with interstitial fluid [18, 42]. Localized blood patches (subcutaneous hematoma) were observed on inner sides in 3/5 (60%) and 1/2 (50%) of Fb-P (samples 1, 3, and 5) and Fb-PECM (1), likely due to the surgical procedure [43]. No signs of swelling were noticed.…”
Section: Resultsmentioning
confidence: 99%
“…In university hospital, KBG was used for treating hematoma in emergency department (60). Kumanomido et al reported that KBG diminished subcutaneous hematoma after surgery in a case report (61). RCT also suggests that in elderly subjects, KBG improved deep vein thrombosis of lower limb (62).…”
Section: Varicose Vein Hematoma and Deep Vein Thrombosismentioning
confidence: 99%